Impact of climate change on water balance of agro ecological units of Kerala - Athul Krishna, K S (Academy of Climate Change Education and Research, 2016)
The research project entitled “Impact of climate change on water balance of agro ecological units (AEUs) of Kerala” was carried out in RARS Pattambi and the daily rainfall data for the period 1991-2014 were collected from 60 stations of Kerala state from the India Meteorological Department, Thiruvananthapurm. Agro Ecological Unit wise information on area and production of various crops were collected fiom Agro Ecology of Kerala, Published by NBSS & LUP and Kerala State Planning Board, 2012. Kerala state, which depends to a great extent on its agriculture for its welfare a detailed knowledge of the Agricultural potential of the region in relation to the climatology of the area is an essential requirement in agricultural planning. In recent decades the increasing population and the resultant higher demands for food have necessitated for optimal exploitation of the available natural resources, in particular, land and water. As the eastern boundary of Kerala is fully bordered by the Western Ghats, the entire state is under the dominant influence of its orography. This results in heavy monsoon rains and large water surplus during a part of the year. This feature combined with the variety of soil types, vegetation classes and geomorphological features result in a diversity of land use patterns. This study assessed the potential impacts of climate change on rainfall and its variations across different agro ecological units as per the projected climate change. To project future climate conditions, the simulation outputs for 2030s, 2050s, and 2080s from seventeen general circulation models (GCMs) were extracted under Intergovernmental Panel on Climate Change (IPCC) greenhouse gases emissions scenario RCP 4.5 to consider the range of uncertainty. Thornthwaite water balance model was estimated to the observed and predicted climate data and this was used to estimate different components of water balance for different agro ecological conditions. This project also studied the impact of climate change on drought, length of growing period and intensity of high rainfall events in the future. The results suggest that future precipitation for the 2030s, 2050s and 2080s are expected to increase based on the multi ensemble GCM outputs. The temporarily and spatial distribution of rainfall like to change significantly throughout Kerala. In nutshell the amount of precipitation during summer and SW monsoon season will expect an increase whereas NE monsoon season and winter season anticipated a decrease in rainfall activity. But the trend is reverse in most of the coastal and high ranges. The total length of growing period is likely to increase in the future due to increased precipitation during summer months. But it can be also noticed that the length of continuous growing period which is a necessity for successful crop production anticipated a decrease. The most interesting observations are the present rain shadow regions of Kerala will going to have a favourable agricultural environment in the future. Studies on impact of climatic change on water balance over the state show that the moisture regime of different AEUs of the state undergo wild fluctuations both in the drier and wetter directions. In general the state is going to witness a hike in evapotranspiration due to increase in temperature as a part of global warming. There is high possibility of flood and drought occurrence in the same calendar year. It can also be inferred that the continuous water surplus period over the state is in a declining trend. It is expected that the results of the present investigation would help in the formulation of climate change adaptive strategies at agro ecological unit level by the judicious management of the available natural resources of land, water and atmosphere. Pointless to say this would enable effective planning for sustainable development of Kerala state.